장애인지원주택 내 장애인 건강관리 지원업무 시 스템 분석: SEIPS framework 기반 포커스 그룹 연구. - 이혜선; 남혜진; 김보혜; 윤주영 (Journal of Korean Academy of Nursing, 2025)
Purpose: This study conducted a work-system analysis using the Systems Engineering Initiative for Patient Safety (SEIPS) framework to assess the flow of health-related information, and the current status of health management tasks for individuals with disabilities (IWD) in supportive housing. Methods: This qualitative study utilized focus groups. Participants included a head of supportive housing, a team leader, a care coordinator and three personal support workers for IWD. Semi-structured interviews were guided by the SEIPS framework to explore the components of persons, tasks, tools and technology, organization, and environments. Results: This study identified five key themes within the five SEIPS components: (1) disparities in role identity and health literacy among staff, (2) challenges in health care support reflecting a person-centered approach, (3) barriers in health-related information exchange and communication tools, (4) needs for organizational strategies or information communication, and (5) needs for integrating health-related information across external healthcare institutions. Additionally, 10 sub-themes were identified. Conclusion: These findings provide a comprehensive system-wide perspective and offer insights into the systematic approaches needed to improve healthcare processes and structures within disability supportive housing. Specifically, healthcare providers and effective tools for integrating health-related information are identified as critical components.